Shared Leadership in Schools: Strategies for Improving Teacher Performance - Rozalinda, Kelly; Ali Marzuki Zebua (STAI Terpadu Yogyakarta, 2024)
This study explores the implementation of shared leadership in schools: Strategies for improving teacher performance. This qualitative case study found that shared leadership in this school was applied through several key indicators, including effective communication, trust given to teachers, staff involvement in decision-making, and the principal's flexibility in responding to change. The principal regularly engaged teachers through meetings to clarify the school's vision and programs, entrusted them with classroom management, and supported online learning during the pandemic. The results show a significant improvement in teacher performance, with key performance indicators such as planning, implementation, and assessment of learning increasing from 57% in 2021 to over 90% in 2023. In 2022, the teacher performance percentage reached 68%-80%, indicating adaptation and improvement in task execution. The peak of performance improvement was achieved in 2023, with over 90% for most indicators. The implementation of shared leadership has proven to support teachers in creating a productive and inclusive learning environment, contributing to the achievement of better educational outcomes in this school.